COVID-19 Epidemic in Malaysia: Epidemic Progression, Challenges, and Response - Hashim, Jamal Hisham; Adman, Mohammad Adam; Hashim, Zailina; Mohd Radi, Mohd Firdaus; Kwan, Soo Chen (Frontiers in Public Health, 2021)
COVID-19 pandemic is the greatest communicable disease outbreak to have hit Malaysia since the 1918 Spanish Flu which killed 34,644 people or 1% of the population of the then British Malaya. In 1999, the Nipah virus outbreak killed 105 Malaysians, while the SARS outbreak of 2003 claimed only 2 lives. The ongoing COVID-19 pandemic has so far claimed over 100 Malaysian lives. There were 2 waves of the COVID-19 cases in Malaysia. First wave of 22 cases occurred from 25th January to 15th February with no death and full recovery of all cases. The ongoing second wave which commenced on 27th February, presented cases in several clusters, the biggest of which was the Sri Petaling Tabligh cluster with an infection rate of 6.5%, and making up 47% of all cases in Malaysia. Subsequently, other clusters appeared from local mass gatherings, and imported cases of Malaysians returning from overseas. Healthcare workers carry high risks of infection. However, 70% of them were infected through community transmission, and not while handling patients. Vulnerable groups, incidence of COVID-19 cases was highest among the 55 to 64 years age group. In term of fatalities, 63% were reported to be aged above 60 years, and 81% had chronic comorbidities such as diabetes, hypertension and heart diseases. Predominant COVID-19 strain in Malaysia is strain B, which is found exclusively in East Asia. However, strain A which is mostly found in the U.S. and Australia, and strain C in Europe, were also present. To contain the epidemic, Malaysia implemented a movement control order (MCO) beginning on 18th March in 4 phases over 2 months, ending on 12th May. In term of economic impacts, Malaysia loses RM2.4 billion a day during the MCO period, with an accumulated loss of RM63 billion up to the end of April. Since 4th May, Malaysia has relax the MCO and open up its economic sector to relieve its economic burden. Currently, the best approach to achieving herd immunity to COVID-19 is through vaccination rather than by acquiring it naturally. However, the vaccine would be a year to a year and a half away.